A Rare but Reversible Cause of Hematemesis: "Downhill" Esophageal Varices. (18th February 2016) - Nguyen, Lam-Phuong; Sriratanaviriyakul, Narin; Sandrock, Christian
Abstract : "Downhill" varices are a rare cause of acute upper gastrointestinal bleeding and are generally due to obstruction of the superior vena cava (SVC). Often these cases of "downhill" varices are missed diagnoses as portal hypertension but fail to improve with medical treatment to reduce portal pressure. We report a similar case where recurrent variceal bleeding was initially diagnosed as portal hypertension but later found to have SVC thrombosis presenting with recurrent hematemesis. A 39-year-old female with history of end-stage renal disease presented with recurrent hematemesis. Esophagogastroduodenoscopy (EGD) revealed multiple varices. Banding and sclerotherapy were performed. Extensive evaluation did not show overt portal hypertension or cirrhosis. Due to ongoing bleeding requiring resuscitation, she underwent internal jugular (IJ) and SVC venogram in preparation for transjugular intrahepatic portosystemic shunt (TIPS), which demonstrated complete IJ and SVC occlusion. She underwent balloon angioplasty with stent placement across SVC occlusion with complete resolution of her varices and resolved hematemesis. "Downhill" varices are extremely rare, though previously well described. Frequently, patients are misdiagnosed with underlying liver disease. High index of suspicion and investigation of alternative causes of varices is prudent in those without underlying liver diseases. Prompt diagnosis and appropriate intervention can significantly improve morbidity and mortality.